FINANCIAL PERFORMANCE ON ACTIVITY MANAGEMENT UNIT (UPK) NATIONAL PROGRAM FOR RURAL COMMUNITY EMPOWERMENT (PNPM-MPD) IN PARANGGUPITO, WONOGIRI 2018-2021 - Diki Setiawan; Simon Nisja Putra Zai (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study measures the performance of activity management units (UPK) based on the 2018-2021 financial statements. This research was conducted in Paranggupito subdistrict, Wonogiri Regency. The data used by this study are secondary data conducted with documentation and interview techniques. This study uses 10 financial measurement ratios, namely income ratio, cost ratio, profit/surplus ratio, fund management effectiveness ratio, borrowing risk ratio, profit allocation ratio, capital growth ratio, group growth ratio, risk-return ratio, and collectability ratio. The results of this study show that in 2018, UPK Paranggupito District had good financial performance and was included in the category of healthy finances, with a percentage of 83.32%. In 2019, it was included in the category of quite healthy, in terms of financial performance with a percentage of 74.99%. In 2020, UPK's financial health was at 83.32% and was included in the healthy category. In 2021, financial performance has a percentage of 79.16% categorized as having a healthy financial performance. This research is a new and alternative assessment model in analyzing financial health and fund management at the sub-district level.